La conception française de la fonction publique - Lemoyne de Forges, Jean-Michel (Array, 2018)
With a total of od 5.5 million employees (or 20% of total employment), out of 67 million inhabitants, France could be classed as a "super administrative" country. However, France must take care of international comparative elements of public service. Namely, the same functions can, according to social and administrative state organization, ensure institutions and people with various types of status. Apart from that, also mentioned is the total number divided into four categories: state public servants in the strict sense (3.850 million, or 70% of the total number), public servants under contract (930,000), army (300, 000) and the complex category of varying legal status (360, 000). Regardless of the variance of their legal status, they are all in the service of the general interest, and are subject to strict deontological rules, especially political and religious neutrality, impartiality and equity.